Transcutaneous vagus nerve stimulation modulates attentional resource deployment towards social cues. (June 2020) - Maraver, Maria J.; Steenbergen, Laura; Hossein, Romina; Actis-Grosso, Rossana; Ricciardelli, Paola; Hommel, Bernhard; Colzato, Lorenza S.
Abstract: Transcutaneous vagus nerve stimulation (tVNS) has been shown to promote inferences of emotional states based on eye-related information provided by facial expressions of emotions. Eye gaze direction can influence the allocation of attentional sources when processing facial emotional stimuli. Here we sought for further evidence indicating whether tVNS effects would be specific to emotional expressions or to gaze - both socially relevant stimuli - and whether they reflect the enhancement of attention. In two separate sessions receiving either active or sham tVNS, forty-three healthy young volunteers completed a Rapid Serial Visual Presentation task in which participants identified the gender of a target face (T1) with direct (salient social cue) or averted gaze (subtler social cue) with different emotional expressions or a neutral expression, and then judged the orientation of a landscape (T2) that appeared at different temporal lags after T1. Active tVNS, compared to sham stimulation, enhanced conditional T2 accuracy for both neutral and emotional faces and independently of the temporal lag, but only when gaze was directed at the participant. This suggests that tVNS modulates attention to a direct gaze (salient social cue) irrespective of the expressed emotion. We interpret that the effects of tVNS seem to reflect enhanced perception of gaze direction, which in turn attracts attention, making the observer more sensitive and increasing the impact of the socially relevant facial cue. We conclude that tVNS is a promising technique for enhancing social information processing in healthy humans. Highlights: tVNS modulates attention to salient social cues. In a RSVP, tVNS enhanced conditional T2 accuracy for stimuli with a direct gaze. The effect is independent of the emotion expressed and the temporal lag. This supports the role of the vagus in processing relevant features of facial expression. tVNS is a promising tool to enhance social functioning in healthy humans.